Jual Beli Online Pada Marketplace Shopee Dalam Tinjauan Etika Bisnis Islam - Arya Wahyu Pradana; Ridho Rokamah (Niqosiya: Journal of Economics and Business Research, 2023)
Economic activity is very closely related to a transaction activity, this is inseparable from an economic concept, namely to fulfill the necessities of life for oneself, for the welfare of the family, and also to help other people around us. Basically online buying and selling sites are buying and selling transactions, which are categorized in the form of modern buying and selling because in practice they apply a technology. Doing business in the view of Islamic business ethics in buying and selling online, sellers are required to always pay attention to ethics in their business, between being kind, speech and actions must be consistent. They are also required to always keep promises, be punctual, not hesitate to admit weaknesses and shortcomings, always maintain the quality of the goods sold, and must not lie and cheat. The purpose of this study was to find out about the implementation of online buying and selling on the marketplace shopee when viewed from Islamic business ethics. This study uses descriptive qualitative research methods by conducting interviews, observation, and documentation. The results of this study say that buying and selling online at the shopee marketplace has done well in implementing the principles of Islamic business ethics, even though understanding related to the principles of Islamic business ethics is still lacking, they are able to do it in their own way and in their own language.